Video Watermarking Scheme Based on Candidates I-frames for Copyright Protection - Rakesh Ahuja; Dr. Sarabjeet Singh Bedi (Institute of Advanced Engineering and Science, 2017)
This paper focuses on moving picture expert group ( MPEG) based digital video watermarking scheme for copyright protection services. The present work implemented the video watermarking technique in which discrete cosine transform (DCT) intermediate frequency coefficients from instantaneous decoder refresh (IDR) frames are utilized. The subset of IDR frames as candidate frames are chosen to reduces the probability of temporal synchronization attacks to achieve better robustness and high visual perceptual quality. A secret key based cryptographic technique is used to enhance the security of embedded watermark. The proposed scheme embedded the watermark directly during the differential pulse code modulation (DPCM) process and extracting through decoding the entropy details. Three keys are required to extract the watermark whereas one of the key is used to stop the extraction process and the remaining two are used to display the watermark. The robustness is evaluated by testing spatial synchronization attacks, temporal synchronization attacks and re-encoding attacks. The present work calculates the simulation results that shows the watermarking scheme achieved high robustness against video processing attacks frequently occur in the real world and perceptibility also obtained without changing the motion vectors during the DPCM process of MPEG-2 encoding scheme.